induction Flashcards
1
Q
sum of all positive integers including n = (n * (n +1)) /2
A
induction hypothesis (n* (n + 1)) /2 1) base s(1) = (1 * (1 + 1)) /2 = (1 * 2) /2 = 2/2 = 1 2) induction case s (k+1) = ((1 * (1 + 1)) /2) + (k+1) common denomator = ((k(k + 1)) /2) + ((2(k+1))/2) = ((k(k +1) + (2(k+1)))/2 factor out (k+1) = ((k+1)(k+2))/2 turn k+2 to k+1+1 = ((k+1)((k+1)+2))/2 []
2
Q
(*) For n > 1, 2 + 2^2 + 2^3 + 2^4 + … + 2^n = 2^n+1 – 2
A
base case (1) s(1) = 2^1 = 2 = 2^(n+1) – 2 = 2^(1+1) – 2 = 2^2 – 2 = 4 – 2 = 2 2) induction case Let n = k + 1.
2 + 2^2 + 2^3 + 2^4 + ... + 2^k + 2^(k+1) = [2 + 2^2 + 2^3 + 2^4 + ... + 2^k] + 2^(k+1) = [2^(k+1) – 2] + 2^(k+1) there are 2 * 2^(k+1) = 2 × 2^(k+1) – 2 raise 2^1 is 2 = 2^1 × 2(k+1) – 2 multiply powers = 2^(k+1+1) – 2 transitive plus brackets = 2^(k+1)+1 – 2
3
Q
For n > 1, 1×2 + 2×3 + 3×4 + … + (n)(n+1) = (n)(n+1)(n+2)/3
A
Let n = 1
Then the left-hand side of () is 1×2 = 2
and the right-hand side of () is (1)(2)(3)/3 = 2
Let n = k + 1. The left-hand side of (*) then gives us:
1×2 + 2×3 + 3×4 + … + (k)(k+1) + (k+1)((k+1)+1)
= [1×2 + 2×3 + 3×4 + … + (k)(k+1)] + (k+1)((k+1)+1)
= [(k)(k+1)(k+2)/3] + (k+1)((k+1)+1)
= (k)(k+1)(k+2)/3 + (k+1)(k+2) = (k)(k+1)(k+2)/3 + 3(k+1)(k+2)/3 = (k+3)(k+1)(k+2)/3 = (k+1)(k+2)(k+3)/3 = (k+1)((k+1)+1)((k+1)+2)/3